Analysis of the Implementation of Criminal Sanctions for Narcotics Crimes in Indonesia - Salsabilla, Putri Icha; Diwangga, Awal; Nasution, Asfrianda Mulia; Ayu, Fitri; Rayfades, Akbar; Rafsanjany, Mu’ammar; Matondang, Maulidya Mora (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This research aims to analyze the legal foundations and sanctions for drug abuse according to fiqh jinayah. This research is a normative juridical legal study with a qualitative approach that analyzes the sanctions for narcotics offenses in national law and Islamic law. Data were collected through literature study and analyzed descriptively, comparatively, and normatively. The collected data were then analyzed using qualitative descriptive methods. Fiqh jinayah in Islamic law provides room for the imposition of sanctions against drug abuse through the taʿzir approach using the qiyas method by equating narcotics with khamr because both have the same illah, which is intoxicating and damaging to the mind. The form of this sanction is adjusted according to the level of damage (mafsadat) caused, which can include flogging, rehabilitation, imprisonment, or even the death penalty for major traffickers. Thus, Islamic law through fiqh jinayah remains relevant and adaptive in responding to contemporary issues such as drug abuse, while adhering to sharia principles and the welfare of the community.